Bioactive vapor deposited calcium‐phosphate silica sol–gel particles for directing osteoblast behavior. Issue 9 (2nd May 2016) - Snyder, Katherine L.; Holmes, Hallie R.; McCarthy, Connor; Rajachar, Rupak M.
Abstract: Silica‐based materials are being developed and used for a variety of applications in orthopedic tissue engineering. In this work, we characterize the ability of a novel silica sol vapor deposition system to quickly modify biomaterial substrates and modulate surface hydrophobicity, surface topography, and composition. We were able to show that surface hydrophobicity, surface roughness, and composition could be rapidly modified. The compositional modification was directed towards generating apatitic‐like surface mineral compositions (Ca/P ratios ∼1.30). Modified substrates were also capable of altering cell proliferation and differentiation behavior of preosteoblasts (MC3T3) and showed potential once optimized to provide a simple means to generate osteo‐conductive substrates for tissue engineering. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 104A: 2135–2148, 2016.